Konsep Merkantilisme dalam Sejarah Pemikiran Ekonomi dan Realisasinya dalam Perspektif Ekonomi Islam - Suriyani; Nurwana (Yayasan Darussalam Patalassang, 2025)
The relevance of mercantilist thinking in the context of modern economics by reviewing the criticisms and alternatives offered by Islamic economics. Mercantilism, as an early economic paradigm that emphasizes the accumulation of national wealth through the hoarding of precious metals and control of trade, is considered to have fundamental weaknesses because it ignores the dimensions of morality, justice, and social welfare. The purpose of this article is to identify how Islamic economic views evaluate the orientation of mercantilism and offer a more balanced economic model. This study uses a qualitative approach by examining theoretical concepts related to Islamic economic principles and critiques of economic structures based on state wealth accumulation. The results of the discussion show that the mercantilist orientation tends to cause inequality and exploitative economic practices, while Islamic economics emphasizes distributive justice, trade ethics, and a balance between material and spiritual interests. This study concludes that Islamic economics provides a more humane and sustainable alternative framework in responding to the structural weaknesses of mercantilism. This research has implications for the development of a contemporary economic model that is capable of combining moral values with economic efficiency, while also serving as a reference for policymakers in formulating a more just and inclusive economic system.